The AgResults Nigeria Aflasafe TM Challenge Project: 2019 Annual Report - International Institute of Tropical Agriculture; Akande, A.; Bandyopadhyay, Ranajit; Ortega Beltran, A.; Falade, Titilayo D.O.; Okpachu, G.; Shenge, K.; Cotty, P.J. (International Institute of Tropical Agriculture, 2020)
This report documents the key activities that were carried under the AgResults Aflasafe Pilot Project during the 2018/ 2019 maize-growing season on the verification process to trigger premium payments for successfully harvested and aggregated Aflasafe™-treated maize.